Hubungan Rhinitis Alergi Terhadap Prestasi Belajar - Muhammad Anfasha Admar (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Allergic rhinitis is the most common form of chronic rhinitis. More than 10% of the world's population suffers from allergic rhinitis. The impact of allergic rhinitis on academic performance is still unclear. Objective: This study aims to determine the impact of allergic rhinitis on academic performance. Method: Reviewing literature that has been published in national and international journals with the keywords allergic rhinitis, academic performance, and quality of life on databases such as NCBI, Pubmed, and Google Scholar which its title and abstract is assessed for relevance, then it was used as a source for the paper. Result: Detrimental impact of allergic rhinitis on academic performance appeared on severe allergic rhinitis and uncontrolled allergic rhinitis, while on the contrary individuals with mild or controlled allergic rhinitis experience elevated academic performance, this could be explained because most allergic rhinitis occurs in developed countries and urban areas, which has a highly competitive culture. Conclusion: There is a significant relationship between allergic rhinitis with academic performance